Seamlessly Splicing Metallic SnxMo1−xS2 at MoS2 Edge for Enhanced Photoelectrocatalytic Performance in Microreactor. Issue 24 (16th November 2020) - Shao, Gonglei; Lu, Yizhen; Hong, Jinhua; Xue, Xiong‐Xiong; Huang, Jinqiang; Xu, Zheyuan; Lu, Xiangchao; Jin, Yuanyuan; Liu, Xiao; Li, Huimin; Hu, Sheng; Suenaga, Kazu; et al.
Abstract: Accurate design of the 2D metal–semiconductor (M–S) heterostructure via the covalent combination of appropriate metallic and semiconducting materials is urgently needed for fabricating high‐performance nanodevices and enhancing catalytic performance. Hence, the lateral epitaxial growth of M–S Sn x Mo1− x S2 /MoS2 heterostructure is precisely prepared with in situ growth of metallic Sn x Mo1− x S2 by doping Sn atoms at semiconductor MoS2 edge via one‐step chemical vapor deposition. The atomically sharp interface of this heterostructure exhibits clearly distinguished performance based on a series of characterizations. The oxygen evolution photoelectrocatalytic performance of the epitaxial M–S heterostructure is 2.5 times higher than that of pure MoS2 in microreactor, attributed to the efficient electron–hole separation and rapid charge transfer. This growth method provides a general strategy for fabricating seamless M–S lateral heterostructures by controllable doping heteroatoms. The M–S heterostructures show increased carrier migration rate and eliminated Fermi level pinning effect, contributing to their potential in devices and catalytic system. Abstract : The epitaxial growth of metal–semiconductor (M–S) Sn x Mo1− x S2 /MoS2 heterostructure is precisely prepared with in situ growth of metallic Sn x Mo1− x S2 at semiconductor MoS2 edge via one‐step chemical vapor deposition method. The oxygen evolution photoelectrocatalytic performance of the epitaxial M–S heterostructure is 2.5 times higher than that of pure MoS2 in microreactor, attributed to the efficient electron–hole separation and rapid charge transfer.